2019
DOI: 10.5747/ca.2019.v15.n4.a307
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and forage behavior of bees in Italian pumpkin crop (Cucurbita pepo)

Abstract: The aim of this experiment was to study the biodiversity of pollinators in Italian pumpkin crop in 2013, 2014 and 2015, in relation to the visiting insects in male and female flowers, the type of collection and their forage behavior, in Ribeirão Preto, SP. The opening and closing of flowers and the attractiveness of the male flowers to the female flowers were evaluated. The frequency and type of collection of flower visitors were obtained by counting in the first 10 minutes of each hour with three replicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Nicodemo, Couto, Braga, and De Jong (2007) observed 2.2 male flowers for each female flower in a pumpkin crop (Cucurbita maxima). Malerbo-Souza et al (2019) studying the Italian pumpkin (C. pepo) for three years (2013, 2014 and 2015) found a ratio of 3.2:1, on average.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicodemo, Couto, Braga, and De Jong (2007) observed 2.2 male flowers for each female flower in a pumpkin crop (Cucurbita maxima). Malerbo-Souza et al (2019) studying the Italian pumpkin (C. pepo) for three years (2013, 2014 and 2015) found a ratio of 3.2:1, on average.…”
Section: Resultsmentioning
confidence: 99%
“…spinipes stingless bees have been observed in many agricultural crops collecting nectar and/or pollen without causing harm and were considered an important pollinator and can even be used as a commercial pollinator (Hickel & Ducroquet, 2000). T. spinipes were important in the pollination of free-range pumpkin (Curcubita mixta) (Lattaro & Malerbo-Souza, 2006) and Italian pumpkin (C. pepo) (Malerbo-Souza, Andrade, Medeiros, Silva, & Siqueira, 2019). No studies were found that evaluated the foraging behavior of T. spinipes in the pollination of the chayote, thus, we hypothesize that these bees are important in the pollination of this cucurbit crop.…”
Section: Introductionmentioning
confidence: 95%